The use of remote sensing technique in investigating the progress of land subsidence (Scientific Journal of Research Studies in Future Civil Engineering, 2023)
Today, overuse of natural resources is one of the issues raised in the world and in Iran. The increasing progress of science and technology as well as excessive use of natural resources have caused problems and endangered environmental resources. Discussions related to sustainable development and its goals as well as optimal design from the point of view of safety and security of environmental parameters are important in the process of construction and operation of a project. Therefore, the aim of the current research is to identify the environmental parameters that influence the subsidence of the earth, which mainly uses the remote sensing technique to prepare these information layers. The research method has been carried out in the form of in-depth study and document content analysis; The results of document content analysis obtained in this research show that vegetation, underground water level and density of wells, etc. are environmental parameters that influence land subsidence. According to the results of surveys, areas with high density of wells and lower underground water level have more subsidence.